2017
DOI: 10.1146/annurev-environ-102016-060726
|View full text |Cite
|
Sign up to set email alerts
|

Material Flow Accounting: Measuring Global Material Use for Sustainable Development

Abstract: The growing extraction of natural resources and the waste and emissions resulting from their use are directly or indirectly responsible for humanity approaching or even surpassing critical planetary boundaries. A sound knowledge base of society's metabolism, i.e., the physical exchange processes between society and its natural environment and the production and consumption processes involved, is essential to develop strategies for more sustainable resource use. Economy-wide material flow accounting (MFA) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 145 publications
(168 reference statements)
3
93
0
15
Order By: Relevance
“…In order to be able to capture displacement effects related to imports and exports, we include a consumption-based indicator in the framework. For this purpose, Eurostat (2017a) provides the indicator raw material consumption (RMC), which is similar to the material footprint (Wiedmann et al 2015) and measures global material use associated with domestic final consumption (Krausmann et al 2017a). The final pair of scale indicators takes the flow of secondary materials into account, which is not presented in conventional ew-MFA indicators: On the input side, the indicator PM measures the sum total of DMC plus the input of secondary materials, and on the output side, IntOut measures wastes and emissions before materials for recycling and downcycling are diverted.…”
Section: Deriving Mass-based Indicators For a Circular Economymentioning
confidence: 99%
See 2 more Smart Citations
“…In order to be able to capture displacement effects related to imports and exports, we include a consumption-based indicator in the framework. For this purpose, Eurostat (2017a) provides the indicator raw material consumption (RMC), which is similar to the material footprint (Wiedmann et al 2015) and measures global material use associated with domestic final consumption (Krausmann et al 2017a). The final pair of scale indicators takes the flow of secondary materials into account, which is not presented in conventional ew-MFA indicators: On the input side, the indicator PM measures the sum total of DMC plus the input of secondary materials, and on the output side, IntOut measures wastes and emissions before materials for recycling and downcycling are diverted.…”
Section: Deriving Mass-based Indicators For a Circular Economymentioning
confidence: 99%
“…Generally, for ew-MFA a systematic assessment of uncertainty is in its infancy (Patrício et al 2015;Laner et al 2014). It has been shown that material flow accounts using different sources and estimation procedures typically differ in their results for global DE by approximately 5% to 20% Krausmann et al 2017a;Fischer-Kowalski et al 2011). For waste statistics, harmonization of data reporting across countries is a major challenge, and data quality differs across EU28 countries (Tisserant et al 2017;Nicolli et al 2012).…”
Section: Validation and Sensitivity: How Robust Are The Derived Circumentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that compared the direct material input per unit of GDP between 1975 and 1995 among different countries, Brazil and Venezuela were the only countries that exhibited an upward trend (Amann et al, 2002). With the exception of Saudi Arabia, Brazil is the country that has reduced its energy intensity the least between 1990 and 2005, as compared to other G20 member states (Abramovay, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Unused extraction and quarry waste due to mining and quarrying activities are considered to have potential environmental impacts (Krausmann, Schandl, Eisenmenger, Giljum, & Jackson, 2017;Torres, Brandt, Lear, & Liu, 2017) and generate local anthropogenic disturbance, especial for construction minerals (Yoshida, Fishman, Okuoka, & Tanikawa, 2017). Nevertheless, data are fairly limited (Eurostat, 2018;Fisher-Kowalski, Krausmann, Giljum, & Lutter, 2011), with only a few MFA inventories even partially considering these type of flows (Kapur et al, 2009;Low, 2005).…”
mentioning
confidence: 99%